El controvertido teniente asesor don Joseph de Medeiros. Un funcionario real en la periferia del Imperio: Salta, siglo XVIII - Aramendi, Barbara Marisa (2013)
In this paper we present a study of Joseph de Medeiros, an officer working for the Intendency of Salta in order to analyze his actions as regards his double position between the interests of the crown he was representing and those of the local elites. We focus our attention on the relations and the conflicts that Joseph de Medeiros created as officer and as member of the local society, thereby analyzing the functioning of the Bourbon administration in a peripheral place. We define Medeiros’s itinerary and reconstruct the networks he formed in order to visualize the administrative organization from the point of view of interpersonal relations. We are interested in analyzing the evidence of the opposing power networks in which Medeiros participated as an active part, and which evidently put in danger his capacity to govern.